Sabiá: Portuguese Large Language Models - Pires, Ramon; Abonizio, Hugo; Almeida, Thales Sales; Nogueira, Rodrigo (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
As the capabilities of language models continue to advance, it is conceivable that “one-size-fits-all” model will remain as the main paradigm. For instance, given the vast number of languages worldwide, many of which are low-resource, the prevalent practice is to pretrain a single model on multiple languages. In this paper, we add to the growing body of evidence that challenges this practice, demonstrating that monolingual pretraining on the target language significantly improves models already extensively trained on diverse corpora. More specifically, we further pretrain GPT-J and LLaMA models on Portuguese texts using 3% or less of their original pretraining budget. Few-shot evaluations on Poeta, a suite of 14 Portuguese datasets, reveal that our models outperform English-centric and multilingual counterparts by a significant margin. Our best model, Sabiá-65B, performs on par with GPT-3.5-turbo. By evaluating on datasets originally conceived in the target language as well as translated ones, we study the impact of language-specific pretraining in terms of 1) capturing linguistic nuances and structures inherent to the target language, and 2) enriching the model’s knowledge about a domain or culture. Our results indicate that most benefits stem from the domain-specific knowledge acquired through monolingual pretraining. Finally, we show that our optimized model for Portuguese demonstrates a reduced performance in English tasks, thereby substantiating the inherent compromise in refining models for specific linguistic domains.